Driving and off‐road impairments underlying failure on road testing in Parkinson's disease. Issue 14 (24th October 2013) - Devos, Hannes; Vandenberghe, Wim; Tant, Mark; Akinwuntan, Abiodun E.; De Weerdt, Willy; Nieuwboer, Alice; Uc, Ergun Y.
ABSTRACT Parkinson's disease (PD) affects driving ability. We aimed to determine the most critical impairments in specific road skills and in clinical characteristics leading to failure on a road test in PD. In this cross‐sectional study, certified driving assessment experts evaluated specific driving skills in 104 active, licensed drivers with PD using a standardized, on‐road checklist and issued a global decision of pass/fail. Participants also completed an off‐road evaluation assessing demographic features, disease characteristics, motor function, vision, and cognition. The most important driving skills and off‐road predictors of the pass/fail outcome were identified using multivariate stepwise regression analyses. Eighty‐six (65%) passed and 36 (35%) failed the on‐road driving evaluation. Persons who failed performed worse on all on‐road items. When adjusted for age and gender, poor performances on lateral positioning at low speed, speed adaptations at high speed, and left turning maneuvers yielded the best model that determined the pass/fail decision (R2 = 0.56). The fail group performed poorer on all motor, visual, and cognitive tests. Measures of visual scanning, motor severity, PD subtype, visual acuity, executive functions, and divided attention were independent predictors of pass/fail decisions in the multivariate model (R2 = 0.60). Our study demonstrated that failure on a road test in PD is determined by impairments in specific driving skills and associated with deficits in motor, visual, executive, and visuospatial functions. These findings point to specific driving and off‐road impairments that can be targeted in multimodal rehabilitation programs for drivers with PD. © 2013 International Parkinson and Movement Disorder Society